VEGETATION ANALYSIS AND POPULATION STRUCTURE OF PLANTS AT MOUNT ENDUT FORESTED AREA, GUNUNG HALIMUN SALAK NATIONAL PARK, BANTEN, JAVA, INDONESIA - Edy Sambas; Cecep Kusmana; Lilik Budi Prasetyo; Tukirin Partomihardjo (REINWARDTIA, 2018)
SAMBAS, E. N., KUSMANA, C., PRASETYO, L. B. & PARTOMIHARDJO, T. 2018. Vegetation analysis and population structure of plants at Mount Endut forested area, Gunung Halimun Salak National Park, Banten, Java,Indonesia. Reinwardtia 17 (1): 39–53. — Study of vegetation structure and species composition at Mount Endut was carried out by using transect and plot methods. Data of trees, saplings and seedlings were enumerated from four transects measuring 10 m × 2,000 m in four directions of slopes i.e. North, South, East and West. In total there were 180 species of trees and saplings belonging to 105 genera and 51 families. Tree density and basal area indicate the variation and the differences in each of the sampling locations. Density of saplings and abundance of seedlings tend to be low in locations with high density and basal areas at tree level. Tree species having higher Importance Value were Castanopsis acuminatissima, Schima wallichii, C. argentea, Quercus gemelliflora, and Altingia excelsa. Castanopsis acuminatissima, Garcinia rostrata, S. wallichii, Symplocos cochinchinensis, and Prunus arborea were saplings which had highest density, while Ophiorrhiza marginata, Cyathea contaminans, Pinanga coronata,C. acuminatissima, and G. rostrata were the most abundant listed seedlings at the study site. At least 27 tree species (21.91%) were recorded as relatively rare (presence represented by only 1–2 individuals), thus requiring special attention in the management of the area.